Health-related quality of life assessment in contemporary phase III trials in advanced colorectal cancer. (November 2016) - Adamowicz, Krzysztof; Saad, Everardo D.; Jassem, Jacek
Highlights: HRQOL has been formally assessed in 36% of recent phase III trials in advanced CRC. A significant gain in HRQOL was found in 39% of trials. There is a significant decrease in the use of HRQOL as an endpoint in phase III trials in advanced colorectal cancer. It is questionable whether HRQOL results may largely help select between competing treatments in this disease. Abstract: Background: Health-related quality of life (HRQOL) is often used as an endpoint in cancer clinical trials. We assessed the frequency and correlates of HRQOL use in phase III trials in advanced colorectal cancer. Methods: We searched PubMed for phase III trials published between January 1998 and December 2014, as well as for companion papers reporting on HRQOL separately. We excluded papers reporting on correlative biology or prognostic factors in isolation from the main trial results, as well as trials on supportive care and on local therapy. Results: We retrieved 111 trials that enrolled a total of 61, 531 patients in 241 trial arms. HRQOL was reportedly used as an endpoint in 40 trials (36%), in all but two as a secondary endpoint. There was a significant decrease in the use of HRQOL, with frequencies of 46% in trials published between 1998 and 2006, and 27% between 2007 and 2014 ( P = 0.04). Trials with HRQOL as endpoint were significantly larger than trials without such endpoint. Formal statistical comparisons involving HRQOL parameters were reported in 36 of 40 trials (90%) with HRQOL assessment, with a significant difference between arms found in 14 (39%), six of which favoring the experimental arm. HRQOL gains were usually accompanied by improvements in efficacy endpoints, but were not related to the number of patients or chemotherapy line. Conclusions: HRQOL has been formally assessed in about one-third of recent phase III trials in advanced colorectal cancer, with a significant gain in HRQOL in about 40% of cases. It is questionable whether HRQOL results may largely help select between competing treatments. This assumption may be one of the reasons for the apparent decreased use of HRQOL as an endpoint in phase III trials in this disease.